Plastination: a contribution to orthopedic surgery teaching in small animals (Veterinary Science, 2017)
The teaching of surgical techniques in under graduated courses requires materials which will allow the students to develop psychomotor skills to perform surgical procedures of osteosynthesis. The authors evaluated the benefits of the use of plastinated specimens in the teaching of the surgical resolution of femoral fractures. Twenty two students who were taking the Surgical Technique and Pathology Course, School of Veterinary Sciences-National University of LaPampa. The students worked in pairs, playing the roles of surgeon and assistant, to reduce and stabilize a transversal diaphisiary fracture of a canine femur previously plastinated using the retrograde intramedular pinning technique. The material was satisfactorily evaluated by means of students opinion surveys, and the graphic register of the experience corroborated the possibility to perform the technique described in the bibliography in the plastinated specimens. All the pairs of students acted as members of a surgical team, reducing and stabilizing the fracture in a satisfactory way. 80% of the surveys found similarities between the plastinated specimens and the real ones. The authors have found that of the six procedures required to solve a fracture, the reduction procedure is the only one that cannot be performed in a similar way to reality. They conclude that 1plastinated models offer a valid model for undergraduates who need to acquire psychomotor skills and to be trained in the performance of intramedular pinning procedures.
Keywords: Dog; Surgery; Orthopaedic; Plastination